The effect of initiation of antiretroviral therapy on monocyte, endothelial and platelet function in HIV‐1 infection. Issue 10 (25th June 2015) - O'Halloran, JA; Dunne, E; Gurwith, MMP; Lambert, JS; Sheehan, GJ; Feeney, ER; Pozniak, A; Reiss, P; Kenny, D; Mallon, PWG
<x xml:space="preserve">Abstract</x> Objectives Monocyte activation, endothelial dysfunction and platelet activation all potentially contribute to the increased risk of cardiovascular disease (CVD) reported in those with HIV‐1 infection. To date, no study has examined how initiation of antiretroviral therapy (ART) affects markers of all three processes. We aimed to compare markers of monocyte, endothelial and platelet function between untreated HIV‐positive subjects and HIV‐negative controls and to examine the early effects of ART initiation on these markers. Methods We measured monocyte [soluble CD14 (sCD14) and sCD163], endothelial [von Willebrand factor (vWF), intercellular adhesion molecule‐1 (ICAM‐1) and vascular adhesion molecule‐1 (VCAM‐1)] and platelet [soluble P‐selectin (sP‐selectin), soluble CD40 ligand (sCD40L) and soluble glycoprotein VI (sGPVI)] biomarkers before and at weeks 4 and 12 post ART initiation in HIV‐positive and well‐matched HIV‐negative controls. Results We examined 40 subjects, 25 HIV‐positive subjects and 15 controls, with a median age of 34 years [interquartile range (IQR) 31, 40 years], of whom 60% were male and 47.5% Caucasian. Pre‐ART, all biomarkers (monocyte, endothelial and platelet) were significantly higher in HIV‐positive patients versus controls (all P < 0.05) and decreased with ART initiation, except for sCD14, which remained unchanged [median 1680 (IQR 1489, 1946) ng/mL at week 12 versus 1570 (IQR 1287, 2102) ng/mL at week 0; P = 0.7]. Although platelet activation markers reduced to levels comparable to those in controls, endothelial dysfunction markers remained elevated, as did sCD163 [at week 12, median 1005 (IQR 791, 1577) ng/mL in HIV‐positive patients versus 621 (IQR 406, 700) ng/mL in controls; P < 0.0001]. Conclusions ART initiation resulted in reductions in levels of CVD‐associated biomarkers; however, although they improved, markers of endothelial dysfunction and monocyte activation remained elevated. How these persistent abnormalities affect CVD risk in HIV infection remains to be determined.